Biodiversity of Nematode spcies composition in land cockroaches in Tam Dao national park, Vinh Phuc province - Luc, Pham Van; Dung, Bui Thi; Hien, Hoang Van (Academia Journal of Biology, 2012)
By using Skrjabin method, 9 of 15 individuals of land cockroaches collected in Tam Dao national park were recorded as hosts infected with nematodes, infection intensity ranged from 3-70 worms/individual. Six nematode species were identified, described and illustrated, that belong to 2 families, 6 genus of order Oxyurida, such as, Aoruroides philippinensis (Chitwood et Chitwood, 1933); Thelastoma periplaneticola Leibersper, 1960; Leidynemella panesthiae (Gabeb, 1878) Chitwood & Chitwood, 1934; Travassosinema morobecola Hunt, 1993; Hammerschmidtiella diesingi (Hammerschmidt, 1938) Chitwood, 1932 and Blatticola blattae (Graeffe, 1860) Chitwood, 1932. Of those, two species were found very common in land cockroaches, namely Aoruroides philippinensis and Hammerschmidiella diesingi. This is the first data on species composition of parasitic nematodes reared from land cockroaches of Vietnam